2012
DOI: 10.1039/c1ce06002c
|View full text |Cite
|
Sign up to set email alerts
|

Formate modulated solvothermal synthesis of ZIF-8 investigated using time-resolved in situ X-ray diffraction and scanning electron microscopy

Abstract: Time-resolved investigations using in situ energy-dispersive X-ray diffraction in tandem with ex situ scanning electron microscopy revealed that solvothermal crystallisation of ZIF-8 in methanol solvent and in the presence of sodium formate as a simple monodentate ligand (modulator) is a rapid process yielding big, high-quality single crystals in short time (<4 h). Kinetic analysis of crystallisation curves was performed by applying the Avrami-Erofe'ev and Gualtieri models. The analyses revealed that the weakl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
273
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 309 publications
(295 citation statements)
references
References 41 publications
21
273
1
Order By: Relevance
“…2d and e). XRD results showed that new emerging diffraction peaks matched well with the standard diffraction pattern of ZIF-8 powders 19 (ESI-3 †) so that the formed layer indeed belonged to ZIF-8 phase. Moreover, the membrane displayed a strong intensity of the (011) reflection in relation to other reflections, thus indicating a preferred crystal orientation of the (011) planes parallel to the support.…”
supporting
confidence: 54%
“…2d and e). XRD results showed that new emerging diffraction peaks matched well with the standard diffraction pattern of ZIF-8 powders 19 (ESI-3 †) so that the formed layer indeed belonged to ZIF-8 phase. Moreover, the membrane displayed a strong intensity of the (011) reflection in relation to other reflections, thus indicating a preferred crystal orientation of the (011) planes parallel to the support.…”
supporting
confidence: 54%
“…A detailed description of the synthesis and the characterization of the ZIF-8 material obtained may be found in Refs. (Cravillon et al 2012;Bux et al 2009). …”
Section: Methodsmentioning
confidence: 96%
“…Further addition of mim leads to the formation of well-defined single-crystal with twelve hexagon {110} and six rhombic {100} exposed faces. 8 The ligand mim exists in two equivalent tautomeric forms, because the proton can be located on either of the two nitrogen …”
Section: ¹1mentioning
confidence: 99%